Escape rooms' pedagogical potential from female future teachers’ perspectives - Hunt-Gómez, Coral; Moreno_Fernández, Olga; Moreno-Crespo, Pilar; Ferreras-Listán, Mario (Journal of University Teaching and Learning Practice, 2020)
Fast and easy Internet and knowledge access by just a click are some of the characteristics of the twenty first century. This means that this knowledge has been acquired fast and superficially. Thus, discernment turns into something ephemeral, because there is not a profound examination of the aspects dealt with. This is caused by the enormous quantity of information found that, in many cases, does not reflect reality. In this sense, teachers can find multitasking students that can perform many activities but without reflexively undertaking them. Education tries to solve these type of problems so the learning-teaching process is as significant as possible. Therefore, future teachers should always have tools for keeping students’ attention, as well as to raise interest in the studied subjects. Within these new tools, escape rooms are, because they not only increase students’ motivation but also encourage teamwork and reflexive learning, as the tasks to be solved are complex. However, as male and female present different perspectives towards gamification, in this work, escape rooms have been studied applying a gender perspective. In the University of Seville, Spain, a descriptive-interpretative exploratory study took place intending to analyse future female teachers’ conceptions about escape rooms. A 17-item questionnaire was applied to 99 female students of the Degree in Primary Education. Results show that subjects highly valued the ludic part of the escape rooms as a didactic activity, which fosters significant learning. Students also appreciated that the activity was close to their reality and that it was integrating students’ interests in the Primary Education classroom. The main conclusion of the study is that, even if there is room for improvement and there is a need to make them more appealing to female students, escape rooms are considered an excellent educative resource as well as an adequate alternative teaching methodology.